2018
DOI: 10.1103/physrevb.98.134308
|View full text |Cite
|
Sign up to set email alerts
|

Thermally deactivated energy transfer in Bi3+Yb3+

Abstract: Y 2 O 3 codoped with Bi 3+ and Yb 3+ is considered as an efficient downconversion material combining strong broadband absorption of Bi 3+ with photon splitting by cooperative energy transfer from Bi 3+ to two Yb 3+ neighbors. However, evidence for photon splitting is lacking. Here we investigate the Bi 3+-to-Yb 3+ energy-transfer mechanism. For cooperative energy transfer the Yb 3+-concentration-dependent luminescence decay will show clear characteristics of cooperative dipole-dipole transfer. Analysis of Yb 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…This, as we will discuss further, is of particular interest and importance for the MPL@PCM composites design. In addition, the up-converting optical properties of the RE ions like the Yb 3+ [183,302], Er 3+ /Yb 3+ [303], and Er 3+ /Tm 3+ /Yb 3+ [304] can sometimes be modified by Bi 3+ ion. Although the number and type of Bi 3+ MPLs are also not plentiful as compared to those RE-based MPLs, they are desirable for the photocatalytic purposes due to the broad and host-dependent persistent range (Figure 8).…”
Section: Ns 2 -Type Cation-doped Mplsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, as we will discuss further, is of particular interest and importance for the MPL@PCM composites design. In addition, the up-converting optical properties of the RE ions like the Yb 3+ [183,302], Er 3+ /Yb 3+ [303], and Er 3+ /Tm 3+ /Yb 3+ [304] can sometimes be modified by Bi 3+ ion. Although the number and type of Bi 3+ MPLs are also not plentiful as compared to those RE-based MPLs, they are desirable for the photocatalytic purposes due to the broad and host-dependent persistent range (Figure 8).…”
Section: Ns 2 -Type Cation-doped Mplsmentioning
confidence: 99%
“…These compounds are referred to the up-converted MPLs (UC-MPLs), and they are mostly activated with the 808 nm and 980 nm NIR light. In this case, to realize the UC process in UC-MPLs, it generally needs an Yb 3+ ion that efficiently absorbs the 980 nm NIR photons or an Nd 3+ ion that can absorb the 808 nm NIR photons [40,135,143,193,[302][303][304][343][344][345][346][347][348][349][350][351][352][353][354][355][356][357][358][359].…”
Section: Nir-converted Mplsmentioning
confidence: 99%
“…Besides, breakthrough of NIR‐DC was achieved in Er 3+ and/or Ho 3+ singly doping, where an incident UV/green photon is split into two or more photons re‐emitted at ≈1530 and 1200 nm, respectively. [ 39a–c,40,71 ] Such kind of efficient NIR splitters well meet the requirement of narrow‐bandgap solar cells like CuInSe 2 , GaSb, and Ge, IR lasing, optical communication, etc. Till now, a series of multi‐photon splitting were reported in Dy 3+ , Tm 3+ , Pr 3+ , and Nd 3+ singly doping, [ 39d–j,72 ] where a maximum QY was evaluated to be greater than 300%.…”
Section: Fundamental Aspectsmentioning
confidence: 99%
“…Yu et al further reviewed the dependence of MR rate (W NR ) on energy gap for Ln 3+ ions in various hosts Figure 7c, and found that only in hosts with low phonon energies, such as fluorides, chlorides, and bromides, W NR of the 4 I 9/2 excited state would be equal to or slower than the radiative transition rates (W R ). [40] Besides, dependence of W NR /W R ratio of Er 3+ 4 I 9/2 level on phonon energy in some classical hosts Figure 7d indicates that hosts with phonon energy < 350-450 cm -1 and/or with special luminescence environment would endow long-lived Er 3+ 4 I 9/2 state for effective three-photon cutting in Er 3+ -doping systems. [76] and c) NIR regions to distinguish the photon-splitting process; Reproduced with permission.…”
Section: N-photon (N ≥ 3) Nir-dc Of Single Ln 3+ Heavy Dopingmentioning
confidence: 99%
See 1 more Smart Citation